Attack detection and secure state estimation for cyber-physical systems with finite-frequency observers. Issue 17 (November 2020) - Su, Qingyu; Fan, Zhongxin; Long, Yue; Li, Jian
Abstract: This paper deals with the malicious attack detection and secure state estimation for linear cyber-physical systems (CPSs). By the exploration of the undetectable attack and indistinguishable attack for CPSs, characterizations on both attacks are proposed. Moreover, based on this characterization, the detectability and distinguishability for CPSs are obtained. Then, sufficient conditions related to the detectable and distinguishable attack are concluded. For the purpose of attack detection, this paper employs a Luenberger observer (detector) in a finite frequency domain. By means of the finite-frequency detector, secure state estimation is accomplished through remove some attacks and sensors. Finally, a numeric example is proposed to verify the validity and effectiveness of the proposed method.